Legal Analysis of Criminal Responsibility for Perpetrators of Murder and Abandonment of Babies from Illicit Relationships - Ahmad Maulana; Risdalina Risdalina; Kusno Kusno (International Journal of Science and Environment (IJSE), 2026)
Case Number 36/Pid.B/2024/PN KFM tried defendant Lusia Neno Kolo, who was accused of committing the crime of murder against her newborn baby. The charges filed included Article 340 of the Criminal Code (premeditated murder), Article 342 of the Criminal Code (murder of a child by a mother due to fear of being discovered pregnant), and alternative charges in the Child Protection Law. The panel of judges ultimately sentenced her to 7 years in prison based on evidence under Article 342 of the Criminal Code. This article analyzes the legal construction, the judge's considerations, the proven elements of the crime, and the relevance of the post-mortem and forensic evidence in the case. Evidence in the form of testimony from the midwife, a visum et repertum, and the results of the Forensic Laboratory (DNA) which showed a 99.999% probability that the baby was the defendant's biological child, became important evidence that strengthened the elements of the crime.